From superior contrast to super resolution label free optical microscopy - Nikhil Jayakumar; Balpreet Singh Ahluwalia (npj Imaging)
Abstract Label-free optical microscopy utilizes the information encoded in light scattered off unlabeled particles to generate the images. This review article starts off with a discussion on how this light matter interaction gives rise to the issues of poor-contrast and diffraction-limited spatial resolution. Then, this article reviews the various far-field label-free optical microscopy techniques that have been developed, with an emphasis on the physical mechanisms behind the image formation processes in such techniques. Thus the article aims to elucidate the various state-of-the-art label-free techniques and their current applications.